ANALISIS FAKTOR KEJADIAN TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS PANDAN KABUPATEN TAPANULI TENGAH - Faisal; Minton Manalu (Poltekkes Kemenkes Medan, 2025)
Tuberculosis (TB) is a very important and serious public health problem worldwide and is a disease that causes a global emergency. TB is the 13th leading cause of death globally and the leading cause of death from infectious diseases after the Covid-19 virus, even higher than HIV/AIDS. The WHO found that the number of TB patients worldwide reached 10.6 million in 2022. Indonesia is the second-largest contributor of TB cases (10%) after India (27%). The estimated TB incidence in Indonesia in 2021 was 969,000 or 354 per 100,000 population. Deaths due to TB are estimated at 144,000 or 52 per 100,000 population. The Tapanuli Tengah District Health Office recorded 750 TB cases in 2022. For the Pandan Community Health Center, the number of TB cases in 2022 was 38 with 2 deaths. The occurrence of TB is strongly influenced by host and environmental factors. This study aims to identify the risk factors for TB occurrence in the Working Area of Pandan Community Health Center, Central Tapanuli Regency. The outcomes of this study include publications in nationally accredited journals and learning modules. The results of the study indicate that the risk factors for TB occurrence in the Working Area of Pandan Community Health Center, Central Tapanuli Regency, are gender (p value = 0.438, OR = 1.714), knowledge (p value = 0.034, OR = 3.755), and residential density (p value = 0.747, OR = 1.522), ventilation area (p value= 0.045, OR= 6.000), and type of floor (p value= 1.000, OR= 1.144). Meanwhile, factors that are not considered risk factors for TB occurrence in the Pandan Community Health Center Work Area, Central Tapanuli Regency are age (p value= 0.182, OR= 0.306), nutritional status (p value= 0.144, OR= 0.345), and smoking status (p value= 0.211, OR= 0.412). It is expected that future researchers will examine in more depth the variables that are not associated with TB occurrence in this study. Keywords: tuberculosis, risk factors.